Verbs of Motion: Semantic Fields and Constructions at a Crossroads - Žic Fuchs, Milena (Array, 2011)
The relationship between syntagmatic and paradigmatic phenomena is analyzed in English Verbs of Motion. More precisely, the semantic field of ‘verbs of walking’ is depicted on the basis of typical constructions in which these verbs appear in the English language. The most frequent verb 'walk' shows the capability of three typical constructions while verbs more removed from the prototypical ‘walk’ show this capability to a lesser degree. In other words, the more removed the verb is from the prototype, the lesser its capability of appearing in typical constructions with ‘walk’. The application of constructions in determining semantic field/category structure provides a concrete mechanism for confirming intuitive judgments native speakers have about semantic field/category membership of Verbs of Motion.